Effect of coronary artery dynamics on the wall shear stress vector field topological skeleton in fluid–structure interaction analyses. Issue 1 (16th March 2023) - Carpenter, Harry J.; Ghayesh, Mergen H.; Zander, Anthony C.; Psaltis, Peter J.
Abstract: In this paper, we investigate the impact of coronary artery dynamics on the wall shear stress (WSS) vector field topology by comparing fluid–structure interaction (FSI) and computational fluid dynamics (CFD) techniques. As one of the most common causes of death globally, coronary artery disease (CAD) is a significant economic burden; however, novel approaches are still needed to improve our ability to predict its progression. FSI can include the unique dynamical factors present in the coronary vasculature. To investigate the impact of these dynamical factors, we study an idealized artery model with sequential stenosis. The transient simulations made use of the hyperelastic artery and lipid constitutive equations, non‐Newtonian blood viscosity, and the characteristic out‐of‐phase pressure and velocity distribution of the left anterior descending coronary artery. We compare changes to established metrics of time‐averaged WSS (TAWSS) and the oscillatory shear index (OSI) to changes in the emerging WSS divergence, calculated here in a modified version to handle the deforming mesh of FSI simulations. Results suggest that the motion of the artery can impact downstream patterns in both divergence and OSI. WSS magnitude is also decreased by up to 57% due to motion in some regions. WSS divergence patterns varied most significantly between simulations over the systolic period, the time of the largest displacements. This investigation highlights that coronary dynamics could impact markers of potential CAD progression and warrants further detailed investigations in more diverse geometries and patient cases.